2000
DOI: 10.1152/jn.2000.83.4.2022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperbaric Oxygen Treatment on Nitric Oxide and Oxygen Free Radicals in Rat Brain

Abstract: Oxygen (O(2)) at high pressures acts as a neurotoxic agent leading to convulsions. The mechanism of this neurotoxicity is not known; however, oxygen free radicals and nitric oxide (NO) have been suggested as contributors. This study was designed to follow the formation of oxygen free radicals and NO in the rat brain under hyperbaric oxygen (HBO) conditions using in vivo microdialysis. Male Sprague-Dawley rats were exposed to 100% O(2) at a pressure of 3 atm absolute for 2 h. The formation of 2,3-dihydroxybenzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 34 publications
3
73
0
4
Order By: Relevance
“…In our calculations, the estimated K m value for O 2 was 240-245 μM when the concentration of the other substrate, L-arginine, was varied from 10 to 200 μM. This result is in agreement with the high experimental K m value for NOS1 that has been reported for O 2 (260 μM) [26], although an even higher value (350 μM) was also reported [27].…”
Section: Sensitivity Of No Production To O 2 Tensionsupporting
confidence: 90%
“…In our calculations, the estimated K m value for O 2 was 240-245 μM when the concentration of the other substrate, L-arginine, was varied from 10 to 200 μM. This result is in agreement with the high experimental K m value for NOS1 that has been reported for O 2 (260 μM) [26], although an even higher value (350 μM) was also reported [27].…”
Section: Sensitivity Of No Production To O 2 Tensionsupporting
confidence: 90%
“…This is true not only for neurovascular studies, but also more broadly for studies involving signaling pathways sensitive to O 2 or to reactive oxygen species. For example, neuronal NOS is sensitive to O 2 concentration (K m O 2 of 350 μM, equivalent to ∼266 mm Hg) (30), and high O 2 may alter NO-mediated synaptic regulation in brain slice preparations (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate inactivation of NO by superoxide but are inconsistent with autooxidation of NO as a mechanism behind cerebral vasoconstriction during HBO. However, several studies have demonstrated an increase in rat brain nitrite/ nitrate concentration during HBO exposure to 5.0 ATA (18,35) or 3.0 ATA (13). In addition, it has been proposed that autooxidation is of physiological importance when the concentration of oxygen greatly exceeds (by Ͼ6 orders of magnitude) that of superoxide.…”
Section: Ach Relaxation and Enos Activity During Hbo Exposurementioning
confidence: 99%